No difference in paired associative stimulation induced cortical neuroplasticity between patients with mild cognitive impairment and elderly controls. Issue 2 (February 2016) - Lahr, Jacob; Peter, Jessica; Minkova, Lora; Lauer, Eliza; Reis, Janine; Heimbach, Bernhard; Hüll, Michael; Normann, Claus; Nissen, Christoph; Klöppel, Stefan
Highlights: First report on paired associative stimulation (PAS) in mild cognitive impairment (MCI) patients. No difference in PAS induced long-term potentiation (LTP)-like neuroplasticity between MCI patients and elderly controls. No correlation between PAS effects and markers of cognitive decline. Abstract: Objective: Paired associative stimulation (PAS) is a widely used transcranial magnetic stimulation (TMS) paradigm to induce synaptic long-term potentiation (LTP)-like plasticity in the intact human brain. The PAS effect is reduced in Alzheimer's dementia (AD) but has not yet been assessed in patients with mild cognitive impairment (MCI). Methods: PAS was assessed in a group of 24 MCI patients and 24 elderly controls. MCI patients were further stratified by their cognitive profile as well as hippocampal atrophy and Apolipoprotein E (ApoE) genotype. Results: There was no difference in PAS effects between MCI patients and healthy controls. MCI patients tended to show a higher response rate and an average PAS effect. PAS effects were not correlated with markers of disease severity or ApoE genotype but were more pronounced in individuals with shorter sleep duration and in MCI subjects with higher ratings of subjective alertness. Conclusions: Contrary to our initial hypothesis, there was no clear difference in PAS between MCI patients and healthy controls. Significance: Our results argue against a continuous reduction of LTP-like plasticity along the spectrum of clinical MCI when stratified by MCI-subtype, APOE genotype or hippocampus atrophy.